2011
DOI: 10.1007/s00253-011-3751-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and quantification of Clostridium kluyveri from the bovine rumen

Abstract: A strain of Clostridium kluyveri was isolated from the bovine rumen in a medium containing ethanol as an electron donor and acetate and succinate (common products of rumen fermentation) as electron acceptors. The isolate displayed a narrow substrate range but wide temperature and pH ranges atypical of ruminal bacteria and a maximum specific growth rate near the typical liquid dilution rate of the rumen. Quantitative real-time PCR revealed that C. kluyveri was widespread among bovine ruminal samples but was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 20 publications
7
121
5
Order By: Relevance
“…This behavior is reflected in carboxylic acids productivities where~3-fold higher values were obtained in the pertractive system (0.26 g/L/h) compared to batch extractive (0.09 g/L/h). The pertractive productivity value in this work is the highest reported for the simultaneous production of VFAs using a mono-culture organism from sugars, greater than those obtained from sucrose 0.23 g/L/h [20] and glucose 0.13 g/L/h [21] considering both BA and HA or from acetate and ethanol 0.18 g/L/h [13] and galactitol 0.08 g/L/h [14] for exclusive HA production.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This behavior is reflected in carboxylic acids productivities where~3-fold higher values were obtained in the pertractive system (0.26 g/L/h) compared to batch extractive (0.09 g/L/h). The pertractive productivity value in this work is the highest reported for the simultaneous production of VFAs using a mono-culture organism from sugars, greater than those obtained from sucrose 0.23 g/L/h [20] and glucose 0.13 g/L/h [21] considering both BA and HA or from acetate and ethanol 0.18 g/L/h [13] and galactitol 0.08 g/L/h [14] for exclusive HA production.…”
Section: Discussionmentioning
confidence: 70%
“…Choi et al [20] reached a combined BA and HA titer of 32.0 g/L from sucrose in liquid-liquid extractive fermentation also by M. elsdenii. Bacterial co-cultures and mono-culture fermentations of C. kluyveri using acetate and ethanol as carbon sources produced HA titers of < 10 and 12.8 g/L, respectively [13,15,18,19] and Clostridium sp. BS-1 has been reported to produce up to 32 g/L of HA in 16 days from galactitol.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the populations of Clostridia, C. kluyveri, and lactic acid bacteria (LAB) in an FPM sample, a quantitative PCR (qPCR) assay was used. The specific primer sets for Clostridia, C. kluyveri, and LAB were SJ-F/SJ-R (18), CloKly1F/CloKly1R (19), and Lac1/Lac2 (20), respectively. The real-time PCR calibration curves for quantifying the above-mentioned microbial taxa were generated via 10-fold serial dilutions of corresponding plasmids (see the text in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a few strict anaerobic bacteria are capable of producing CA through fermentation. For example, Clostridium kluyveri can produce CA using ethanol as the electron donor (Barker and Taha, 1942;Kenealy et al, 1995;Weimer and Stevenson, 2012); Megasphaera elsdenii can produce CA from glucose and sucrose (Choi et al, 2013;Weimer and Moen, 2013); Clostridium sp. BS-1 produces CA using galactitol as the carbon source .…”
mentioning
confidence: 99%